Análise do impacto da integração do BRICS, TICKS e MINT para o Brasil por meio de um modelo de equilíbrio geral - Tamiosso, Rafaela Lauffer Ostermann (Universidade do Vale do Rio dos Sinos, 2018)
The study goal is to analyze the profile and trading opportunities with the BRICS, TICKS, and MINT countries through trade integrations simulations — looking for patterns to identify the most benefited sectors by their technological intensity degree. The methodology used was the bibliography review and the data collecting on AliceWeb/SECEX/MDIC, using the products classification by technological intensity degree according to OCDE criteria. In addition, the computable general equilibrium model was applied with GTAP (version 9). Six simulations were performed between Brazil and the BRICS, TICKS and MINT countries, with 50% and 100% importation tax reductions for each trade agreement. Analysing all trade agreements simulations, the most impacted sector would be that of low technological intensity because it was the most protected at the initial equilibrium. The results show that would be a replacement of Brazilian domestic production to low-cost imports from BRICS, TICKS, and MINT countries, leading to Brazilian exporting growth of primary and low technological intensity products, and an export dropping of products with medium-high and high-end technological intensity. Also, the trade agreements would generate welfare gains for Brazil in all scenarios, however that one related to the TICKS countries, with a large tax reduction, would be the most beneficial for Brazil, with gains of US$ 4.8 billion, also being the agreement with the largest net benefit to the world, reaching US$ 23.9 billion.
Keywords: Integração comercial; MEGC; BRICS; TICKS; MINT; Trade integration; CGE; BRICS; TICKS; MINT; ACCNPQ::Ciências Sociais Aplicadas::Administração